2008
DOI: 10.1097/ajp.0b013e31817bcb65
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial Influence on Exercise-induced Delayed Onset Muscle Soreness at the Shoulder: Pain Catastrophizing and Catechol-O-Methyltransferase (COMT) Diplotype Predict Pain Ratings

Abstract: Objective-The experience of pain is believed to be influenced by psychologic and genetic factors. A previous study suggested pain catastrophizing and catechol-O-methyltransferase (COMT) genotype influenced clinical pain ratings for patients seeking operative treatment of shoulder pain. This study investigated whether these same psychologic and genetic factors predicted responses to induced shoulder pain.Methods-Participants (n=63) completed self-report questionnaires and had COMT genotype determined before per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 52 publications
4
61
0
Order By: Relevance
“…Importantly, COMT genotype and catastrophizing were not related. They have subsequently replicated these findings in a separate clinical cohort and in two additional cohorts experiencing experimentally-induced shoulder pain [7; 8]. The findings of Trost and colleagues of a genetic contribution to catastrophizing opens the possibility that the COMT X catastrophizing interaction may represent a gene-gene interaction in addition to a gene-environment interaction.…”
mentioning
confidence: 89%
“…Importantly, COMT genotype and catastrophizing were not related. They have subsequently replicated these findings in a separate clinical cohort and in two additional cohorts experiencing experimentally-induced shoulder pain [7; 8]. The findings of Trost and colleagues of a genetic contribution to catastrophizing opens the possibility that the COMT X catastrophizing interaction may represent a gene-gene interaction in addition to a gene-environment interaction.…”
mentioning
confidence: 89%
“…For example, previous studies have reported that COMT, OPRM1 , and GCH1 show sex-specific associations with pain responses [14,15,124]. In addition, COMT haplotypes have been shown to interact with psychological functioning (i.e., pain catastrophizing) to predict both experimental and clinical shoulder pain outcomes [58,60]. Research has shown that OPRM1 and COMT exerted combined effects on the total dosage of morphine consumed by patients with chronic cancer-related pain [138].…”
Section: General Considerationsmentioning
confidence: 99%
“…Immediately after collection, samples were centrifuged at 3000 rpm for 15 min to obtain the cell sediment and they were stored at Ϫ20°C until main analysis. We prefer to use saliva instead of blood sampling because salivary collection is a noninvasive, stress-free, and ethic suitable assessment method for children which has been previously used (22,23).…”
Section: Methodsmentioning
confidence: 99%